Insulin, dibutyryl-cAMP, and glucose modulate expression of patatin-like domain containing protein 7 in cultured human myotubes - Miš, Katarina; Lulić, Ana-Marija; Marš, Tomaž; Pirkmajer, Sergej; Katalinić, Maja (Frontiers in Endocrinology, 2023)
Expression of patatin-like phospholipase domain containing protein 7 (PNPLA7), also known as neuropathy target esterase-related esterase (NRE), a lysophospholipase, increases with fasting and decreases with feeding in mouse skeletal muscle, indicating it is regulated by insulin, counterregulatory hormones, such as glucocorticoids and catecholamines, and/or nutrients. In cultured mouse adipocytes insulin reduces Pnpla7 expression, underscoring the possibility that insulin regulates PNPLA7 in skeletal muscle. The first aim of this study was to establish whether PNPLA7 is functionally expressed in cultured human skeletal muscle cells. The second aim was to determine whether PNPLA7 is regulated by insulin, glucocorticoids, cAMP/protein kinase A pathway, and/or glucose. Cultured human skeletal muscle cells expressed PNPLA7 mRNA and protein. Gene silencing of PNPLA7 in myoblasts reduced the phosphorylation of 70 kDa ribosomal protein S6 kinase and ribosomal protein S6 as well as the abundance of α1-subunit of Na+,K+-ATPase and acetyl-CoA carboxylase, indirectly suggesting that PNPLA7 is functionally important. In myotubes, insulin suppressed PNPLA7 mRNA at 1 g/L glucose, but not at low (0.5 g/L) or high (4.5 g/L) concentrations. Treatment with synthetic glucocorticoid dexamethasone and activator of adenylyl cyclase forskolin had no effect on PNPLA7 regardless of glucose concentration, while dibutyryl-cAMP, a cell-permeable cAMP analogue, suppressed PNPLA7 mRNA at 4.5 g/L glucose. The abundance of PNPLA7 protein correlated inversely with the glucose concentrations. Collectively, our results highlight that PNPLA7 in human myotubes is regulated by metabolic signals, implicating a role for PNPLA7 in skeletal muscle energy metabolism.